Bacteriophage control of infectious biofilms - Meneses, Luciana Amorim Perestrelo (2024)
Biofilm formation, a strategy of bacterial survival, is a significant concern in different areas, including health, where infectious biofilms are very difficult to combat with conventional antimicrobial therapies. Bacteriophages, the viruses that infect bacteria, are promising agents to prevent and control biofilm-related infections. This chapter describes a series of standard procedures that can be used to study the potential of bacteriophages for biofilm control, from biofilm formation to bacteriophage treatment and evaluation of its efficacy.